Perancangan Ulang Alat Pengepres Ikan Berbasis Antropometri untuk Meningkatkan Efisiensi Produksi Tepung Ikan pada CV Hasil Laut - Kharisma Putri, Dwi Ratih; Febri Satoto, Handy (SURYA TEKNIKA, 2026)
The fish meal processing industry at the CV scale generally still performs the fish pressing process manually using a lever system, which requires a long time, great operator effort, and produces non-uniform pressing results. This study aims to redesign the fish pressing tool to be more ergonomic using an anthropometric approach so that the tool dimensions match the operators’ body characteristics. Anthropometric data in the form of Standing Shoulder Height (SSH) and Hand Reach (HR) were collected from all operators at the pressing station, then processed through calculations of the mean, standard deviation, data adequacy test, data uniformity test, and percentile calculation. The first percentile was selected so that the tool can be used by operators ranging from the smallest to the largest body size. The processing results determined a tool height of 132.35 cm based on the first percentile of SSH and a working-area depth of 71.82 cm based on the first percentile of HR, with a tool length of 245 cm. The application of these ergonomic dimensions produced a better working posture, reduced bending, and supported increased efficiency of the fish meal production process.